2021
DOI: 10.1155/2021/8882050
|View full text |Cite
|
Sign up to set email alerts
|

HPLC/MS-MS Identification of Oak Quercus aegilops Root Tannins

Abstract: Tannins are natural polyphenolic compounds widely distributed in the plant kingdom in the leaves, bark, fruits, and other parts. They have various biological functions in humans and animals and are used mainly in the pharmaceutical and cosmetic industries. The aim of this work was to isolate, extract, purify, and identify the tannins from the root bark of a common oak tree (Quercus aegilops L.) in Jordan and around the Mediterranean. The results showed that at least one form of ellagitannin (ellagic acid ester… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Recent research revealed that HTs' antioxidant activity may lower insulin‐induced lipogenesis, blood triglycerides, and cholesterol 51 . Notably, the amount of HTs depends on the species, region, and age of the plant 52 . Both NRF and NRL are abundant in HT.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent research revealed that HTs' antioxidant activity may lower insulin‐induced lipogenesis, blood triglycerides, and cholesterol 51 . Notably, the amount of HTs depends on the species, region, and age of the plant 52 . Both NRF and NRL are abundant in HT.…”
Section: Resultsmentioning
confidence: 99%
“…51 Notably, the amount of HTs depends on the species, region, and age of the plant. 52 Both NRF and NRL are abundant in HT. NRL has 2.06 ± 1.54 and 2.80 ± 1.97 mg/g of CRG and PGG, respectively, compared with NRF's 2.50 ± 1.01 and 1.84 ± 2.73 mg/g.…”
Section: Methods Validationmentioning
confidence: 99%